The spirit of democracy : the struggle to build free societies throughout the world - Diamond, Larry 1951- (Times Books/Holt, 2008)
A world partially transformed -- The universal value -- The democratic boom -- The democratic recession -- What drives democracy : the internal factors -- What drives democracy : the external factors -- What drives democracy : the regional influence -- What sustains democracy -- The prospect for global democracy -- Latin America's uneasy progress -- The postcommunist divide -- The Asian exception? -- Africa, overcoming personal rule -- Can the Middle East democratize? -- The path to democratic renewal -- Making democracies work -- Promoting democracy effectively -- Physician, heal thyself